Determinants of Problems in Teenage Pregnancy - Hapisah, Hapisah; Rafidah, Rafidah; Sofia, Norlaila; Mahpolah, Mahpolah (JOSING: Journal of Nursing and Health, 2023)
This study aims to determine the determinants or risk factors for pregnancy complications in adolescents. This type of research is quantitative analytical research with a case-control approach. The results of univariate analysis show that most respondents married at the age of 16-19 years (92%), and the remainder at the age of 12-15 years lived in rural areas (62%) and with their parents. (70). %), have low education (65.3%), have poor economic conditions (56%), and have anemia status (60%). The most frequently experienced pregnancy problems were constant vomiting and not wanting to eat (39.3%), while the least experienced were bleeding at the beginning or end of pregnancy and yellow eyes/skin (1.3% each). There are two variables related to teenage pregnancy problems, namely anemia status and knowledge about pregnancy. The most influential variable is anemia (p=0.000, OR: 3.995 (1.952-8.174). In conclusion, the impact of complications and deaths on women and children and the effect on future generations can be prevented. Keywords: Determinants, Teenage Pregnancy, Problems